A case study on the effect of imagery training for elite archers of South Korea - Kim, Y.; Chang, T. (International Journal of Applied Sports Sciences, 2020)
The present study aimed to test the effect of imagery training based on neurofeedback in elite archers of South Korea. Imagery training was provided to six elite archers, who imagined shooting three arrows in a set for a total of eight sessions. During imagery training, actual sounds recorded from an international archery Competition were played and Neurofeedback training was provided in a laboratory. In order to accurately measure EEG (Electroencephalogram), the archers were sufficiently rested, and the external environments were controlled before training began to prevent interference by artifacts. EEG was measured while the archers performed imagery training; real-time feedback was provided using vibrations when the waveform of beta waves was outside of the threshold determined for each archer. In addition, to test the effect of imagery training, scales assessing sports competitive state anxiety and sports imagery were administered before and after training, and pre-post changes were assessed. The results showed that in all archers, beta waves stabilized and vibration frequency decreased in post-measurement. Anxiety levels were reduced and imagery ability improved. Based on the findings, real-time neurofeedback training is believed to enhance athletes' self-regulation.